Coitus induced colpo evisceration in a 3-months post hysterectomy patient: an unusual tale in gynecology - Ramirez, Fernando P.; Hakizimana, Theoneste; Naranjo, Ubarnel A.; Fajardo, Yarine; Torres, Llanelys de L. A. G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Vaginal dehiscence after pelvic surgery is an extremely rare gynecological emergency world over. Without a high index of suspicion, it can easily be missed with grave consequences. We present an extremely rare case of this post abdominal hysterectomy case for which if immediate suspicion and timely intervention were not ensured, the patient would have suffered serious morbidity and/or death.